A Novel Approach for Cardiotocography Paper Digitization and Classification for Abnormality Detection - Ozturk, Sibel; Sahin, Safiye Agapinar; Aksoy, Ayse Nur; Ari, Berna; Akinbi, Alex (Ieee-Inst Electrical Electronics Engineers Inc, 2023)
Cardiotocography (CTG) is a clinical procedure that is used to track and gauge the severity of fetal distress. Although CTG is the most often used equipment to monitor and assess the health of the fetus, the high rate of false positive results due to visual interpretation significantly contributes to needless surgical delivery or delayed intervention. In this study, a novel approach is introduced where both printing CTG paper is digitized and a machine learning approach is employed to detect the abnormality in the digitized CTG signal. Image processing-based preprocessing steps are employed to make the printing of CTG paper more convenient to extract the CTG signal. Various signal-processing techniques are used to calibrate the extracted CTG signal. Then, Empirical Mode Decomposition (EMD) is used to decompose the CTG signal into its frequency components and instantaneous frequency and spectral entropy features are extracted. After feature normalization and feature selection with ReliefF algorithm, support vector machines (SVM) is used for the classification of the normal and abnormal classes. A novel dataset is used in the experimental works and various performance evaluation metrics are used for the evaluation of the achievement of the proposed method. 10-fold cross-validation-based experiments show that the proposed method is quite efficient in abnormality detection in printing CTG papers where an average accuracy score of around 90.0% is produced.
Keywords: Image color analysis; Feature extraction; Image processing; Signal processing algorithms; Fetal heart rate; Classification algorithms; Prediction algorithms; EMD; feature selection; image enhancement; printing CTG paper; signal reconstruction; SVM classifier